The Reader Response Approach in Modern Language Acquisition - González, Ismel; Courtland, Mary Clare (Journal of the Canadian Association for Curriculum Studies, 2010)
This article describes the implementation of the reader response approach as a focal practice in a university Spanish language class. The design of was qualitative. Methods included participant observation, taped responses, a taped focus group meeting, and analysis of documents. Four main themes emerged from the data analysis: shifting roles in the modern language classroom; patterns of shared response to La Casa en Mango Street; students’ attitudes towards a new pedagogical approach; and response to La Casa en Mango Street. This approach contributed to the narrowing of the gap between language and culture in the modern language classroom.